1999
DOI: 10.3989/gya.1999.v50.i5.679
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of rosemary (<i>Rosmarinus officinalis L.</i>) extracts on natural olive and sesame oils.

Abstract: RESUMEN Actividad antioxidante de extractos de romero (Rosmarinus officinalis L) en aceites de sésamo y de oliva.Se determinaron las actividades antioxidantes de extractos de cloroformo y de metanol de romero (Rosmarinus officinalis L.) en aceites de sésamo y de oliva almacenados a 55 °C mediante medidas de los índices de peróxidos a intervalos regulares. Se utilizaron concentraciones al 1% y 2% de extractos y ácido cítrico. Los extractos (excepto para los días 12,16 y 20 de almacenamiento de aceite de oliva) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Plant originated antioxidants have been used in oils or lipid containing foods in order to prevent oxidative deterioration [52]. Naturally occurring compounds in rosemary plant (in all forms such as ground, extracts, and essential oils) [53,54] have been reported to exhibit antioxidant properties greater than butylhydroxyanisole (BHA) and equal butylhydroxytoluene BHT [52]. The rosemary extract has antibacterial, antifungal, antiviral, antimicrobial, anti-inflammatory, astringent, and spasmolytic activity [55] and even anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Plant originated antioxidants have been used in oils or lipid containing foods in order to prevent oxidative deterioration [52]. Naturally occurring compounds in rosemary plant (in all forms such as ground, extracts, and essential oils) [53,54] have been reported to exhibit antioxidant properties greater than butylhydroxyanisole (BHA) and equal butylhydroxytoluene BHT [52]. The rosemary extract has antibacterial, antifungal, antiviral, antimicrobial, anti-inflammatory, astringent, and spasmolytic activity [55] and even anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Butylated hydroxyanisol (BHA), butylated hydroxytoluene (BHT), gallats and tert-butylhydroquinone (TBHQ) are synthetic antioxidants commonly used in food processing because they provide good protection for unsaturated fat and oils, and they have low cost and high stability (Tsimidou and Boskou, 1994;Özcan and Akgül, 1995;Dapkevicius et al, 1998;Belitz and Grosch, 1999). However, more recently, these substances have been questioned because they show some toxicity and carcinogenecity (Tsimidou and Boskou, 1994;Madsen and Bertelsen, 1995;Gámez-Meza et al, 1999;Özcan, 1999). Therefore, the demand for natural antioxidants has grown in order to render food products safer for mankind.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Autoxidation and lipolysis are responsible for off flavors and chemical spoilage in lipidcontaining foods, and the products formed via these reactions are potentially toxic. 4,5 Antioxidants play an important role in preventing undesirable changes in flavor and nutritional quality of foods. 6 The oxidative stability of oils and fats may be influenced by many factors, such as light, metal ions, temperature, enzymes, and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,16,17 These attempts have led to the development of very effective natural antioxidants from rosemary and sage. 4,[17][18][19][20][21] Maulyanov et al 22 reported that fruits of sumach (R. coriaria L.) contain flavonols, phenolic acids, hydrolyzable tannins, anthocyans, and organic acids. Brunke et al 2 also pointed out that the fruits of sumach contained malic, citric, and tartaric acids.…”
Section: Introductionmentioning
confidence: 99%